Experimental investigation on the performance of transcritical CO2 ejector–expansion heat pump water heater system. (1st July 2018) - Zhu, Yinhai; Huang, Yulei; Li, Conghui; Zhang, Fuzhen; Jiang, Pei-Xue
Highlights: The ejector-expansion heat pump system was investigated for water outlet temperatures up to 90 °C. The COP reaches 3.3 when water outlet temperature is 90 °C. The ejector-expansion system COP is 10.3% higher than the corresponding basic cycle. Adding an ejector is more effective for the generation of high-temperature hot water. The COP and ΔCOP increase when the compressor rotation speed decreases. Abstract: The effects of hot-water outlet temperature, compressor discharge pressure, compressor rotation speed, and expansion valve opening on the ejector and overall system performance were investigated for tap water outlet temperatures ranging from 50 to 90 °C. The coefficient of performance (COP) of the ejector–expansion heat pump system reaches 4.6 when the tap water outlet temperature is 70 °C, which is 10.3% higher than the corresponding basic cycle. Compared to the basic system, adding an ejector is more effective for the generation of high-temperature hot water. The COP of the ejector–expansion heat pump system increases; however, the COP improvement ratio ΔCOP decreases with the increase in the discharge pressure because of lower pressure lift ratio and ejector efficiency. The COP and ΔCOP increase when the compressor rotation speed decreases under our test conditions; simultaneously, the heat capacity decreases.